Clinical characteristics and prognostic factors in multiple myeloma patients with light chain deposition disease. Issue 8 (1st June 2017) - Mohan, Meera; Buros, Amy; Mathur, Pankaj; Gokden, Neriman; Singh, Manisha; Susanibar, Sandra; Jo Kamimoto, Jorge; Hoque, Shadiqul; Radhakrishnan, Muthukumar; Matin, Aasiya; Davis, Cynthia; Grazziutti, Monica; et al.
Abstract: Light chain deposition disease (LCDD) is characterized by monotypic immunoglobulin depositions which will eventually lead to loss of organ function if left untreated. While the kidney is almost always affected, the presence and degree of LCDD in other organs vary. Ten to thirty percent of LCDD patients have underlying Multiple Myeloma (MM), yet outcome and prognostic markers in this particular patient group are still lacking. Here, we analyzed 69 patients with MM and biopsy proven LCDD and report on renal and extra‐renal involvement and its impact on prognosis as well as renal response depending on hematologic response. Coexisting light chain diseases such as AL amyloid and cast nephropathy were found in 30% of patients; those with LCDD and concurrent amyloid tended to have shorter survival. Cardiac involvement by LCDD was seen in one‐third of our patients and was associated with shorter overall survival; such patients also had a significantly higher risk of treatment‐related mortality (TRM) after stem cell transplant (SCT) compared to LCDD patients without cardiac involvement. This study highlights that MM patients with LCDD present with different clinical features compared to previously reported LCDD cohorts. Rapid initiation of treatment is necessary to prevent progressive renal disease and worse outcome. Coexisting light chain diseases and cardiac involvement are more common than previously reported and confer worse clinical outcome, emphasizing the need for careful patient careful patient evaluation and treatment selection.